Qualidade de vida relacionada à saúde de crianças escolares com diagnóstico de asma em Porto Alegre Brasil - Roncada, Cristian (2012)
Introduction: In children with asthma diagnosis, assessment of quality of life related to health has become an important component in measuring the impact of disease on physical, social and mental patients. Objectives: To evaluate the quality of life related to health in children diagnosed with asthma in the city of Porto Alegre. Methods: The study included children diagnosed with asthma, aged eight to 12 years of age. The psychometric properties assessed were reliability through Cronbach s Alpha (α-C) and ceiling & floor effects. The assessment of quality of life was measured by the generic Kindl-R. These measurements and pulmonary function were assessed according to international guidelines. Evaluations of possible associations between the total score of asthmatic children and the clinical and demographic variables were evaluated by linear regression models. Results: The study included 80 children diagnosed with asthma, 51 children (64%) were categorized as white, with education levels between the 1st and 5th grade and the average values of pulmonary function within normal parameters. The value of α-C total score was 0.672. No score values obtained for the floor effect; a few schoolers reached the ceiling effect in some domains, but in ≤6% of cases. Asthmatic children had a lower score in almost all areas of the questionnaire of quality of life compared with healthy children (72.91 vs 75.10 p = 0.041). Adding to this finding, the scores of children diagnosed with asthma and obesity were lower compared to normal children (-0.82 vs -6.00 p = 0.003). Conclusion: The questionnaire of quality of life related to health Kindl-R has proper behavior in the asthmatic population evaluated. Children diagnosed with asthma studied showed a lower score in scores related quality of life compared to healthy children. In addition, children diagnosed with asthma and obese have a lower questionnaire score when compared with normal children. The use of this instrument can provide clinically relevant information for evaluation and monitoring of asthmatic children